2014
DOI: 10.3389/fpls.2014.00435
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptional profiling of Botrytis cinerea genes targeting plant cell walls during infections of different hosts

Abstract: Cell walls are barriers that impair colonization of host tissues, but also are important reservoirs of energy-rich sugars. Growing hyphae of necrotrophic fungal pathogens, such as Botrytis cinerea (Botrytis, henceforth), secrete enzymes that disassemble cell wall polysaccharides. In this work we describe the annotation of 275 putative secreted Carbohydrate-Active enZymes (CAZymes) identified in the Botrytis B05.10 genome. Using RNAseq we determined which Botrytis CAZymes were expressed during infections of let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 118 publications
(207 reference statements)
2
115
0
1
Order By: Relevance
“…Aforementioned studies has also revealed that under cellulose induced condition, the strain has shown preponderance of LPMOs in its secretome (23,36). In our study, we have found that B. cinerea genome harbors nine homologues of LPMOs, seven are upregulated upon cellulosic inductions at transcripts level (Fig 2A).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Aforementioned studies has also revealed that under cellulose induced condition, the strain has shown preponderance of LPMOs in its secretome (23,36). In our study, we have found that B. cinerea genome harbors nine homologues of LPMOs, seven are upregulated upon cellulosic inductions at transcripts level (Fig 2A).…”
Section: Discussionsupporting
confidence: 69%
“…Out of five interacting proteins identified, two were annotated as cellobiose dehydrogenases, and rest belong to proteolytic superfamily. We negated proteolytic proteins such as Prolyl aminopeptidase, Aspartic protease, Pectin methyl esterase, from the list of interacting partner because of two prime reasons: First, secretome of B. cinerea is already enriched with proteases and hydrolases (23) and thus there is high probability of finding these proteins as contaminants in the pull down assays, secondly, these proteolytic protein lack electron donor tendencies. Therefore, two identified cellobiose dehydrogenases i.e., CDH_53425 and CDH_52080 were further analysed to identify potential reductant partner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the S. sclerotiorum – P. vulgaris interaction, SS1G_01493 (beta-xylosidase) was up-regulated during the early stages before the emergence of visible necrotic symptoms on the stem, whereas genes encoding cellulose-degrading enzymes, SS1G_13255 (beta-1,4-glucanase) and SS1G_07146 (cellobiohydrolase), were induced during the later stages of infection coinciding with the formation of visible stem lesions [40]. In B. cinerea , the expression patterns of genes encoding xyloglucan-degrading enzymes was found to be vastly different dependent upon the host plant [58]. …”
Section: Resultsmentioning
confidence: 99%
“…Necrotrophic fungi produce several cell wall degrading enzymes (CWDEs) to degrade plant cell wall polysaccharides that favor plant colonization. Blanco-Ulate and co-authors present a genome-wide transcriptional profiling of Botrytis cinerea CWDEs expressed during infection of important nutritional resources such as lettuce leaves, ripe tomato fruit, and grape berries (Blanco-Ulate et al, 2014).…”
mentioning
confidence: 99%